The Human Resources for Health Program in Rwanda – Reflections on Achievements and Challenges: Comment on "Health Professional Training and Capacity Strengthening Through International Academic Partnerships: The First Five Years of the Human Resources for Health Program in Rwanda" - Delisle, Hélène (Int J Health Policy Manag, 2018)
This commentary is a further discussion of a paper published in this journal on the health professional training initiative led by the Government of Rwanda since 2012 and presented as a case study. According to the authors, the partnership program with international academic institutions may serve as model for other countries to address the shortage of health professionals and to strengthen institutional capacity, based on the competencybased and innovative training programs, the numbers of graduates, the improved quality of health services and institution strengthening. However, the conditions may not be as optimal elsewhere. A supportive government policy, massive funding and an academic consortium comprised of 19 United States academic institutions have contributed to the success of the program. We also noted that the trained professionals were clinicians almost exclusively, at the expense of public health specialists and other health professionals who can better address emerging issues such as non-communicable diseases (NCDs) particularly for their prevention, which is now compelling. Among others, the training of more nutritionists as members of the health team is needed.